Numbers - Awabdy, Mark A., 1981- (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2023)
"This substantive and useful commentary on the book of Numbers explores the contemporary significance of this biblical book"--
Includes bibliographical references (pages 571-608) and indexes.
Keywords: Bible. -- Commentaries